Gender Aspects of Library and Information Profession in Nigeria: Affirmative Action For Males? - Unegbu , Vincent Enyeribe; Opeke, Rosaline O. (MiddleBelt Journal of Library and Information Science, 2013)
A millennial axiom that librarianship is a female profession was to be reconfirmed or otherwise, in this research, in Nigeria. Survey, through phone calls and questionnaire methods, were used in data collection. Data collected was analyzed using simple percentage in tabular form. Some impediments in the profession making men an endangered species based on the work being too routine, not challenging, not appealing, and no opportunity to make extra money were highlighted. Attractions such as librarianship being ICT based, information aspect of librarianship being made robust, and availability of opportunity for training and development both locally and internationally were recommended. Outcome of the survey showed that affirmative action and preferential treatment are not recommended in order to retain male librarians who are fast approaching extinction in the profession. Except on sponsorship, no special preference should be given to attract the males, rather general applicable rules were chosen to make librarianship viable and interesting. Four alternative methods were suggested to keep male librarians afloat in the profession.